The Effect of pH on Methanobactin and Gold Nanoparticle Formation - Hoida, Emily J.; Banks, Alison R. (My University, 2011)
Methanobactin is a biomolecule found in methane-oxidizing bacteria that is involved in the transportation of copper into the cell. Methanobactin can also bind and reduce other atoms as well, including gold. This study examines the effect pH has on the formation of gold nano particles, which form from the reduction of gold (III) ions by methanobactin.
Color poster with diagrams, images, graphs, and charts.
Keywords: Posters; Nanoparticles--Analysis; Gold--Analysis; Methanotrophs; Hydrogen-ion concentration--Effectiveness